Werner & Ingbar's the thyroid : a fundamental and clinical text - Braverman, Lewis E., 1929-; Cooper, David S. (Physician) (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"The most comprehensive textbook on the thyroid appears in an extensively revised 10th edition. This classic text provides comprehensive coverage of every aspect of thyroid anatomy, development, biochemistry, physiology, pathophysiology, and treatment of all thyroid disorders. This edition has a more international group of contributors and new chapters on surgical management of thyroid cancer, thyroid disrupters and thyroid hormone analogs. Chapters address clinical controversies regarding subclinical hypothyroidism and hyperthyroidism"--